MIKROPROPAGASI SUKUN (Artocarpus communis Forst), TANAMAN SUMBER KARBOHIDRAT ALTERNATIF - Supriati, Yati; Mariska, Ika; Hutami, Sri (Research Center for Biology-Indonesian Institute of Sciences, 2005)
Bread fruit (Artocarpus communis Forst) is one of tropical fruit, which has a high contain of carbohydrate.In certain area, it becomes an alternative staple food when the main staple foods are scarce.The amount of carbohydrate in breadfruit is almost the same with the one in sweet potato, but it is higher than in potato. The main constraint of the development of breadfruit is the limited of seedling availability.Tissue culture technique has been known for its excellent result for plant propagation, because this technique has ability in producing seedling in a large quantity, in uniform growth rate and in a relative short time.The experiment was conducted at Cell Tissue Culture Division, Indonesian Center Agricultural Biotechnology and Genetic Resource Research and Development (1CAB1OGRAD) from February 2003 until December 2004.There were some steps experiments with series of combination medium as treatments. The first steps was shoot multiplication at Sk-2 medium with WPM + BA (0; 0,5; 1,0; 1,5 and 2,0 mg/1) + Thidiazuron (0; 0,4 mg/1);The second step was elongation shoot at Sk-3 with WPM + kinetin (1,2 and 3 mg/1) + GAa(0 and 5 mg/1), and the third was root initiation and proliferation, by comparing WPM + IBA (0, 2, 4 and 6 mg/1) + charcoal (0;0,5 %) and WPM (1; 0,5) + BA (0; 1,5 and 5 mg.l) or NAA (1,2 and 3 mg/1). For the step of acclimatization, soil and compost were used in comparison of (1;1 and 1:2).The result showed that the best media for shoot multiplication of breadfruit was WPM + BA 2 mg/1 + TDZ 0 4 with shoot number of 15,5., while the best media for shoot elongation was WPM + Kinetin 1 mg/1 + GA, 5 mg/1.WPM + IBA 3 mg/1 was the best formula for root proliferation with the highest root number about 6.5 and percentage of shoot producing root about 60%. For acclimatization, soil and compost in combination of 1:1 was the best media for planlet of breadfruit with the success rate about 70%. Charcoal is not necessary in root initiation and proliferation.